Accelerating Innovation in China’s Solar, Wind and Energy Storage Sectors - Kuriakose, Smita; Lewis, Joanna; Tamanini, Jeremy; Yusuf, Shahid (World Bank, Washington, DC, 2017)
Green innovation can become a new driver of growth. It can spur economic growth by (a) enhancing productivity in traditional industries by reducing the energy use and lessening the environmental impact; (b) expanding new green industries, such as renewable energy, clean cars, and waste management; and (c) leapfrogging current technology to give rise to new industries. The Chinese government is hopeful that green innovation will substantially enhance growth, and this study explores that potential. The study analyzes a few specific sectors in which China has varying levels of advancement: wind, solar, and energy storage. These sectors have been chosen on the basis of (a) their central role in China’s ability to meet its green growth and greenhouse gas (GHG) reduction goals, (b) China’s continuing large public investment into innovation in these sectors, and (c) the expected availability of data to use in the analysis, including outputs such as patenting and inputs such as public and private investment in research and development (R&D). The government plays an essential role in establishing a conducive environment for green innovation. Given the high fixed costs associated, green sectors are even more dependent on the public sectors and favorable regulatory regimes. The recommendations provided in in this study aim to provide China with more comprehensive support for select green sectors.